Analisis Isi Berita Pembangunan Periklanan dan Kelautan pada Surat Kabar Kaltim Post - Sugiharto, Eko (Jurnal ILMU KOMUNIKASI, 2008)
Abstract: The objectives of this research were to explain the characteristic of the newspaper’s profile of fishery and marine development, to compare the objectiveity of the reports based on the result of censuses of fishery and marine science and mass media experts’ opinions, to study the policy of news on fishery and marine development on Kaltim Post newspaper editorial staff. The respondents were chosen by using purposive sampling method and were supported by disproportional stratifed random sampling method for news sample clipped for evaluation from the panelist expert team. The data obtained was then analyszed by using content analysist method. The research findings show that the subject matter proportion frequency and volume are mainly dominated with news on marketing and the type of writing is dominated with news, it is also dominated with positive tendencies and non-headlines. The panelist expert team and the mass media expert gave much kind of opinion to the news. Based on the census result, the news is presented enough objectively. The reseacrh findings show that news on fishery and marine development is still considered as a minor discourse by Kaltim Post.